The Influence of Product Innovation on Marketing Performance through Iconic Product Advantages of Bead Craft Business Actors in East Kalimantan - Nuraeni, Hera; Indriastuti, Herning; Martiyanti, Dwi (Indonesian Journal of Advanced Research, 2025)
This research is motivated by the challenges faced by bead craft business actors in East Kalimantan, such as competition for similar products, limited promotions, and lack of design innovation that hinders marketing performance. This study aims to analyze the influence of product innovation on marketing performance with the advantages of iconic products as a mediating variable. The method used is a quantitative approach through an online questionnaire survey with purposive sampling technique. Of the 248 populations, 159 respondents were obtained whose data were analyzed using Partial Least Square (PLS). The results show that product innovation has a significant effect on the excellence of iconic products and marketing performance, and the relationship between the two is significantly mediated by the excellence of iconic products. These findings affirm the importance of local culture-based innovation in strengthening the competitiveness and sustainability of the bead craft business.